SOCIALIZATION OF THE THREE BIG SINS IN EDUCATION AT PGRI ROGOJAMPI VOCATIONAL SCHOOL, BANYUWANGI REGENCY: SOSIALISASI TIGA DOSA BESAR PENDIDIKAN DI SMK PGRI ROGOJAMPI KABUPATEN BANYUWANGI - Auliya Gaffar Rahman; Widhya Putriana; Andi Wapa (Yayasan Bakti Cendekia Nusantara, 2025)
: This community service program aims to contribute to improving the image of the educational sector through efforts to prevent and address various social issues that frequently occur in educational settings and society, particularly bullying, sexual violence in schools, and intolerance. The implementation method employed educational approaches, socialization, and community empowerment by involving relevant stakeholders. The results indicate that bullying behavior has complex root causes, including peer influence, family environment, and individual social status, with significant negative impacts on victims’ physical and mental health. Bullying prevention efforts can be carried out through the wise use of technology, the cultivation of compassion values, the avoidance of discriminatory attitudes, socialization through creative media, and the enforcement of strict regulations. Furthermore, sexual violence in the school environment is a critical issue that requires serious attention, as schools should be safe spaces for students. Continuous preventive education and the establishment of special task forces within schools are considered essential to ensure student safety. Intolerance in society was also identified as a factor that can potentially lead to conflict and disrupt social harmony. The proposed solutions include internal efforts through community empowerment and the active role of religious and community leaders, as well as external efforts through government support, law enforcement, and the utilization of social media as an effective and accessible tool for disseminating messages of tolerance. This community service activity is expected to serve as a reference for creating safe, inclusive, and equitable educational and social environments